The Detection of BRAF-V600E Mutation in Hairy Cell Leukaemia by Polymerase Chain Reaction and Study of its associated Clinicohaematological Parameters - Iqbal, Muhammad Ijaz; Robert, Helen Mary; Khan, Nabeela; Mahmood, Rafia; Khurshid, Ayesha; Khan, Saleem Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To contemplate the occurrence of a rare mutation (BRAF V600E) in the patients having Hairy cell leukemia in our setting, which wouldserve asuseful analytic and diagnostic criteria.Study Design: Analytical cross sectional study.Place and Duration of Study: Armed Forces Institute of Pathology Rawalpindi Pakistan, from Oct 2017 to Oct 2018.Methodology: A sample of 36 patients with a suspicion of Hairy cell leukemia were included in this investigation. Complete blood counts, bone marrow examination (trephine biopsy and aspiration), cyto-chemistry and staining of the patients suspected to have Hairy cell leukemia was performed. PCR was done for detection of BRAF V600E mutation.Results: 29 (80.5%) cases showed a positive BRAF mutational analysis and 7 (19.4%) cases showed a negative result.Conclusion: Almost all the cases of classic Hairy cell leukemia had BRAF V600 E mutation.Isolating this mutation can be used as a regular tool in detection of disease and monitoring disease progression and relapse.